Adat dan Korporasi: Konflik Agraria Tanah Ulayat di Sumatera Barat - Nugroho, Khairana Zata; Ramadhan, Fauzan Syahru; Meliala, Bryna Rizkinta Sembiring (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This article focuses on agrarian conflicts over customary land in West Sumatera between communities and the government representing corporate companies and the steps taken to resolve these conflicts. Conflicts began to arise when the economic value of palm oil increased in the international market. This made many corporations try to expand their business by looking for suitable lands to plant oil palm, including Indonesia. This article aims to find out the problems of agrarian land conflicts and what steps are taken to resolve these conflicts. The method used in preparing this article is the historical method. The historical method is carried out with four stages, namely heuristics, criticism, interpretation, and historiography. From this research, it is known that through various agreements signed between Minangkabau customary leaders and the government representing corporate companies, some customary land in West Sumatera was then used as land for planting oil palm until when the lease expired, there were differences of opinion between the Minangkabau people and the government regarding the existence of the customary land used. Various forms of settlement have been taken in order to resolve agrarian land conflicts, but all these efforts have not resulted in satisfactory decisions so that agrarian land conflicts still continue today.